CLINICOPATHOLOGIC FEATURES OF PROBABLY MALIGNANT ADNEXAL MASSES WITHOUT SIGNS OF ASCITES AND CARCINOMATOSIS - Harika Yumru Çeliksoy; Hamdullah Sözen; Hatice Merve Baktıroğlu; Samet Topuz; Yavuz Salihoglu (İstanbul Tıp Fakültesi Dergisi)
Objective: Our objective was to assess the patients who have probable early stage ovarian cancer. Materal and Method: Between 2010-2018, 208 patients with isolated adnexal masses who underwent surgery due to presumed malignancy were analyzed. We excluded patients with radiologic evidence of ascites and tumour implants. Results: According to the final pathology reports, 52 (25%) of 208 patients had benign tumours, 46 (22%) were borderline, and 110 (53%) patients’ tumours were malignant. The most unexpected benign tumours were serous cystadenofibroma. Of the malignant tumours, 3 were uterine sarcomas, 8 were metastatic ovarian tumours (all gastrointestinal origin), and 99 were primary ovarian cancers. Seventy-six of 99 primary ovarian cancers were epithelial and 23 were nonepithelial. The most common histologic types were respectively serous and endometrioid adenocarcinoma. Seventy-six percent of primary ovarian cancers were early stage (stage 1-2) and 24% were advanced stage (stage 3-4). Conclusion: Patients with a suspicious adnexal mass, even if ascites or carcinomatosis are not existing, have a high rate of malignancy and should be managed considering this risk.